Initial steps for developing large-scale rearing and processing of black soldier flies, Hermetia illucens L., in a start-up bioconversion facility - Weldon, Christopher W. (University of Pretoria, 2024)
Thesis (PhD (Applied Entomology))--University of Pretoria, 2024.